Anticancer, Antibacterial, Antioxidant, and DNA-Binding Study of Metal-Phenalenyl Complexes. (14th April 2022) - Sen, Subhadeep; Chowdhury, Nilkanta; Kim, Tae-Wan; Paul, Mohuya; Debnath, Dilip; Jeon, Seob; Bagchi, Angshuman; Im, Jungkyun; Biswas, Goutam
Abstract : Phenalenyl (PLY)-based metal complexes are a new addition to the metal complex family. Various applications of metal-based phenalenyl complexes (metal-PLY) have been reported, such as catalyst, quantum spin simulators, spin electronic devices, and molecular conductors, but the biological significance of metal-PLY (metal = Co(II), Mn(III), Ni(II), Fe(III), and Al(III)) systems has yet to be explored. In this study, the anticancer properties of such complexes were investigated in ovarian cancer cells (SKOV3 and HEY A8), and the cytotoxicity was comparable to that of other platinum-based drugs. Antibacterial activity of the metal-PLY complexes against both gram-negative ( E. coli ) and gram-positive ( S. aureus ) bacteria was studied using a disk diffusion test and minimum inhibitory concentration (MIC) methods. All five metal-PLY complexes showed significant antibacterial activity against both bacterial strains. The antioxidant properties of metal-PLY complexes were evaluated following the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging method and were acceptable. The DNA-binding properties of these metal-PLY complexes were investigated using absorption spectroscopy, fluorescence spectroscopy, viscosity measurements, and thermal denaturation methods. Experimental evidence revealed that the complexes bind to DNA through intercalation, and the molecular docking study supported this conclusion.